Simulation and Study of Temperature Distribution in Living Biological Tissues under Laser Irradiation - Shurrab, Kawther Mohammad; Sayem El-Daher, Moustafa (Journal of Lasers in Medical Sciences, 2014)
Introduction: With the rapid increase in use of lasers in medical treatments, it is important to understand the mechanisms of heat transfer in biological tissues in order to minimize damage to the tissues resulting from extra heat applied. The aim of this study is to investigate the temperature distribution in living biological tissues when laser irradiation is used in a treatment. Methods: In this work a model was suggested to study the impact of several parameters such as (laser power, exposure time, laser spot size) on the temperature distribution within skin tissues when subjected to a laser source. A three-dimensional finite element thermal model of biological tissues was developed using bio-heat equation to describe heat transfer in living tissues. Results: Temperature distribution within skin tissues subjected to laser heating is calculated in details using the Finite element method and a suggested model; the results are presented in figures and tables showing the effects of Laser spot size, power and exposure time on temperature distribution within treated tissue. Conclusion: the results presented in this work are expected to be useful in optimizing Laser spot size, power and exposure time for a variety of laser applications medicine and surgery.